Dynamics of Simultaneous Local Elections in 2020 During Covid-19 Pandemic - Wahyu Widodo; Werijon Werijon; Agung Setiawan (Politicon : Jurnal Ilmu Politik, 2021)
During the COVID-19 pandemic, it is difficult to ignore the possibility of conflict in the Simultaneous Regional Head Elections; in fact, it tends to grow. Fundamentally, conflicts arise as a result of lack of planning and implementation of Electoral Management Bodies, confusing regulations, overlapping responsibilities and multiple interpretations of laws, and inability to deal with technical electoral issues. This study aims to examine the dynamics of holding the 2020 Simultaneous Regional Head Elections in the midst of the COVID-19 pandemic. This study employs a qualitative design with a descriptive approach. Data collection was carried out using literature review techniques from several related journal sources. According to the results of the study with the Concept of Conflict Resolution, the potential conflicts that emerged in the 2020 simultaneous regional elections, including the existence of money politics disguised as assistance for overcoming COVID-19, low voter participation due to public fear of the transmission of the COVID-19 virus, and weak technical elections management which resulted in the need for re-voting in several regions in Indonesia. Therefore, it can be conluded that Conflict resolution to eliminate money politics culture can be done by conducting political education which must be started from political parties. Meanwhile, to minimize re-voting, Electoral Management Bodies must prepare overall technical management well from planning, organizing, implementing to evaluating the entire process of organizing the election.